Economy of favours in Central Asia: Tanish-bilish, kattalar and kichkina - Rano Turaeva (economic sociology. perspectives and conversations, 2022)
Central Asia has been undergoing economic, political and social transformation in recent decades after gaining independence from the Soviet Union. The challenges have included economic collapse and decaying Soviet infrastructure, as well as political turbulence and global insecurities. As a result, political, economic and social insecurities have increased, as struggles for power and resource grabbing have created what scholars then characterized as bespredel (Turaeva 2014) and a time of chaos (Nazpary 2002). The region is not only an important geopolitical space, but also culturally diverse.
Keywords: 300